Corrosion initiation life prediction of RC square piles based on a dual time-dependent bidirectional chloride diffusion model. (15th March 2021) - Shi, Danda; Chen, Xingwei; Shao, Wei
Highlights: An analytical solution for predicting the bidirectional chloride penetration in RC square piles is proposed. The dual time-dependence of the surface chloride concentration and the chloride diffusion coefficient is considered. The versatility of the proposed analytical solution is validated by comparing the traditional solution. Corrosion initiation life prediction and sensitivity analysis of main parameters are conducted. Abstract: An analytical solution for predicting the bidirectional chloride penetration in reinforced concrete (RC) square piles is proposed by considering the four sides of piles exposed to marine environments. This proposed solution considers the dual time-dependence of the surface chloride concentration and the chloride diffusion coefficient based on the Green function method. The distributions of the surface chloride concentrations for different marine zones along the altitude of square piles are introduced. The versatility of the proposed analytical solution is validated by comparison with the traditional solution considering different conditions and values of the surface chloride concentration and the chloride diffusion coefficient. Furthermore, the proposed solution is applied to predict the corrosion initiation life of RC square piles, and the main factors influencing the corrosion initiation life of piles are also analysed. The results show that the corrosion initiation life of piles in the tidal and splash zones is shortest, while that in the submerged and atmospheric zones becomes longer in turn. The study also indicates that the corrosion initiation life of RC square piles is sensitive to both the material and environmental parameters such as the concrete cover depth and the relative humidity.